2011
DOI: 10.1007/s12263-011-0259-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum selenium and single-nucleotide polymorphisms in genes for selenoproteins: relationship to markers of oxidative stress in men from Auckland, New Zealand

Abstract: There is controversy as to the recommended daily intake of selenium (Se), and whether current New Zealand diets are adequate in this nutrient. Various functional single-nucleotide polymorphisms (SNPs) polymorphisms may affect the efficacy of Se utilisation. These include the glutathione peroxidases GPx1 rs1050450, GPx4 rs713041, as well as selenoproteins SEPP1 rs3877899, SEL15 rs5845, SELS rs28665122 and SELS rs4965373. This cross-sectional study measured serum Se levels of 503 healthy Caucasian men in Aucklan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
73
3
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 57 publications
3
73
3
1
Order By: Relevance
“…Beyond this level, there was no correlation between serum Se and DNA damage in a group of men at high risk for prostate cancer [36]. A recent study by our group has also shown benefits on DNA integrity between serum Se levels of 116 and 149 ng/ml, varying with genotype, among a healthy male population [37]. Serum Se levels have been shown to positively correlate to prostate tissue Se levels [38], and therefore serum Se levels could indicate the ‘seleno-nutrient health’ in prostate tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond this level, there was no correlation between serum Se and DNA damage in a group of men at high risk for prostate cancer [36]. A recent study by our group has also shown benefits on DNA integrity between serum Se levels of 116 and 149 ng/ml, varying with genotype, among a healthy male population [37]. Serum Se levels have been shown to positively correlate to prostate tissue Se levels [38], and therefore serum Se levels could indicate the ‘seleno-nutrient health’ in prostate tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Both groups presented with the moderate selenium deficiency [30]. It has been suggested that maximal activity of selenoenzyme is reached at blood selenium levels above 1.27 µmol/L, or according to the recent research by Rayman plasma selenium levels in the range of 1.6 to 1.9 µmol/L are considered optimal for thyroid and overall good health [31].Also the study by Karunasinghe et al (2012) have suggested that the basic selenium requirement may vary with genotype for a number of variations in selenoprotein genes, suggesting that an effective dietary selenium intake for one person may be different from that for others. In the absence of this information, an elaborate mechanism for concentrating iodine from the circulation and converting it to T4, which is then stored and released on demand.…”
Section: Discussionmentioning
confidence: 97%
“…Volunteers in the study were 24 European women, who were selfassigned into two groups, control group with healthy participants (n=13), and a group of women with Hashimoto's thyroiditis (HT) on medication with L-thyroxine (n=11). Both groups presented with recommended plasma selenium levels should be in the range of 1.27 -1.90µmol/L [32].…”
Section: Methodsmentioning
confidence: 99%
“…Additional mechanisms might be prooxidant and mitochondrial damage, particularly for species such as Se-IV, Se-VI, and Se-Met [26,34,35,36], copper/zinc superoxide-dismutase translocation into mitochondria, and increased inducible nitric oxide synthase [37], DNA damage [38], and P38-P53 activation [39]; all mechanisms are potentially involved in ALS etiopathogenesis [3,40], and more generally functional alterations due to nonspecific incorporation of selenium species into proteins and to adverse effects on lipid metabolism and protein synthesis [41]. …”
Section: Discussionmentioning
confidence: 99%